Public and private health insurance in Germany: The ignored risk selection problem - Martina Grunow; Robert Nuscheler (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2010)
While risk selection within the German public health insurance system has received considerable attention, risk selection between public and private health insurers has largely been ignored. This is surprising since - given the institutional structure - risk selection between systems is likely to be more pronounced. We find clear evidence for risk selection in favor of private insurers. While private insurers are unable to select the healthy upon enrollment they manage to dump high risk individuals who then end up in the public system. This gives private insurers an unjustified competitive advantage vis-à-vis public insurers. A risk adjusted compensation would mitigate this advantage.
Keywords: C13; C23; I10; I18; 330; Risk Selection; Public and Private Health Insurance; Risk Adjustment; Private Krankenversicherung; Gesetzliche Krankenversicherung; Adverse Selektion; Gesundheitsfinanzierung; Deutschland